Daily Living Assistance Provided by Residents to Other Residents in Residential Aged Care Homes: Knowledge, Attitudes, and Practices - Asmuri, Siti Noraini; Kadar, Masne; Razaob, Nor Afifi; Chui, Chai Siaw; Mohd Rasdi, Hanif Farhan (UI Scholars Hub, 2022)
Background: The rise of the aged population in Malaysia has resulted in the increased need for services, especially in terms of healthcare. Hence, continuous support is crucial to managing the daily living activities of this group. This study aimed to identify the knowledge, attitudes, and practices of older adults residing in Malaysian aged care homes concerning daily living activities and their provision of assistance to other residents with more significant disabilities. Methods: Semi-structured interviews were conducted on ten older adults and six staff members of two selected residential aged care homes. The interview session concerned the knowledge, attitudes, and practices of older people related to the basic activities of daily living (BADL) and instrumental activities of daily living (IADL). We also applied a qualitative content analysis method. Results: Three themes emerged after the interviews: (1) knowledge of older adults on BADL and IADL (highest response); (2) attitudes toward the assistance given to other residents; (3) types of assistance given to other residents and the staff. Conclusions: The knowledge, attitude, and practices related to the assistance in activities of daily living by older adults may contribute to the development of a program or module that can fulfill the needs of other residents with more significant disabilities, especially in aged care homes.